1998
DOI: 10.1046/j.1365-3083.1998.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

RANTES Production in HIV‐1 Antigen‐Stimulated Whole Blood Culture: Relationship with Type 1 Immune Response and Plasma Viral Load in Individuals Infected with HIV‐1

Abstract: Host factors which control replication and clearance of human immunodeficiency virus (HIV) are poorly understood. RANTES (regulated on activation, normal T cell expressed and secreted) and other beta-chemokines may be HIV-1-suppressive factors but their role in the progression of HIV-1 infection is a subject of controversy. We investigated the relationship between production of RANTES and correlates of disease progression in 15 patients infected with HIV-1. We used whole blood culture to study the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…2 and 3 is similar to what is seen for a number of other chemokines, such as MCP-3, and is, as noted in Results, also consistent with the general pattern of expansion and reduction in granuloma size during this time (34,51). For RANTES, published data have also associated induction with type 1 responses (3,24,26,42). For lymphotactin, there is little information on its expression in models of disease.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3 is similar to what is seen for a number of other chemokines, such as MCP-3, and is, as noted in Results, also consistent with the general pattern of expansion and reduction in granuloma size during this time (34,51). For RANTES, published data have also associated induction with type 1 responses (3,24,26,42). For lymphotactin, there is little information on its expression in models of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary observations have also shown a preferential infection of Th1 and Th2 cells by R5 and X4 isolates, respectively, when viral entry is measured in the first 24 h [156]. However, R5 viral replication and spread in Th1 cells was not as efficient as that in Th2 cells, perhaps due to the increased ␤-chemokine secretion in Th1 cells [32,80,81].…”
Section: T Helper 1 Vs T Helper 2 Cellsmentioning
confidence: 99%
“…For example, it has been shown that RANTES can participate in activation of HIV-1-specific CD8 ϩ cytotoxic activity via CCR3 [79] and that MIP-1␣, MIP-1␤, and RANTES are preferentially associated with type 1 immune responses [32,80,81]. That these ␤-chemokines can also preferentially recruit T helper 1 cells to potential sites of inflammation [82,83] suggests the existence of a positive feedback loop that links the production of viral suppressive chemokines to type 1 immune responses.…”
Section: Chemokines and Hiv Infectionmentioning
confidence: 99%
See 2 more Smart Citations